High Mortality of HLH in ICU Regardless Etiology or Treatment - Bichon, Amandine; Bourenne, Jérémy; Allardet-Servent, Jérôme; Papazian, Laurent; Hraiech, Sami; Guervilly, Christophe; Pauly, Vanessa; Kaplanski, Gilles; Mokart, Djamel; Gainnier, Marc; Carvelli, Julien (Frontiers in Medicine, 2021)
Background: Adult hemophagocytic lymphohistiocytosis (HLH) is highly lethal in the ICU. The diagnostic and therapeutic emergency that HLH represents is compounded by its unknown pathophysiological mechanisms. Here, we report on a large cohort of adult HLH in the ICU (ICU-HLH). We analyzed prognostic factors associated with mortality to define the diagnostic and therapeutic challenges in this specific population. Methods: This retrospective study included adult patients diagnosed with HLH in four ICUs in Marseille, France between 2010 and 2020. Patients with a clinical diagnosis of HLH and who fulfilled the HLH-2004 criteria (> 4/8) and/or had an HScore > 169 were diagnosed with HLH. HLH was categorized into four groups according to etiology: sepsis-associated HLH, intracellular infection-associated HLH, malignancy-associated HLH, and idiopathic HLH. Results: 260 patients were included: 121 sepsis-associated HLH (47%), 84 intracellular infection-associated HLH (32%), 28 malignancy-associated HLH (11%), and 27 idiopathic HLH (10%). The ICU mortality rate reached 57% (n = 147/260) without a statistical difference between etiological groups. Independent factors associated with mortality in multivariate analysis included age (OR (5 years) = 1.31 [1.16- 1.48], p < 0.0001), SOFA score at ICU admission (OR = 1.37 [1.21-1.56], p < 0.0001), degradation of the SOFA score between ICU arrival and HLH diagnosis (Delta SOFA) (OR = 1.47 [1.28-1.70], p < 0.0001), the presence of bone-marrow hemophagocytosis (OR = 5.27 [1.11-24.97], p = 0.04), very severe anemia (OR = 1.44 [1.09-1.91], p = 0.01), and hypofibrinogenemia (OR = 1.21 [1.04-1.41], p = 0.02). Conclusions: In this large retrospective cohort study of critically ill patients, ICU-HLH in adults was associated with a 57% mortality rate, regardless of HLH etiology or specific treatment. Factors independently associated with prognosis included age, presence of hemophagocytosis in bone-marrow aspirates, organ failure at admission, and worsening organ failure during the ICU stay. Whether a rapid diagnosis and the efficacy of specific therapy improve outcome is yet to be prospectively investigated.